An Averroistic Text on Intellect: The Treatise Entitled De Intellectu by Abū Muḥammad Abdallāh Ibn Rushd. - Dugan, Mehmet (Cumhuriyet Ilahiyat Dergisi / Cumhuriyet Theology Journal, 2026)
During the High Scholastic period, the majority of discussions concerning the intellect were conducted with the aim of avoiding conflict with Christian thought. Alongside this, some thinkers were also interested in how this issue could be treated from a purely philosophical perspective. In this sense, Averroes' Long Commentary on the De anima of Aristotle (LCDA) is one of the influential and controversial philosophical texts that triggered intense debates on the nature of the intellect in the thirteenth-century Latin world. This study concerns a short treatise known in Latin as De intellectu and attributed to the son of Averroes, Abū Muḥammad 'Abdallāh. Although an Arabic copy of the treatise has survived to the present day, its Latin and Hebrew translations circulates widely in Europe. Indeed, in some collections, more than one copy is preserved. This situation shows that the treatise was regarded important in certain respects by Christian and Jewish scholarly circles. Similarly, the fact that this treatise was translated into Latin in the first half of the thirteenth century also indicates the intense interest of Christian thinkers in the question of the intellect. The treatise deals briefly and concisely with the analogy between intellect and sense perception, the activity of the active intellect, and the relation between potentiality and actuality. Arguments on these matters are strengthened by quotations from Alexander of Aphrodisias and Themistius, early commentators on Aristotle. This study examines whether the treatise reflects an Averroist conception of the intellect. In this context, the treatise is compared with the third book of the LCDA, which was translated into Latin in the thirteenth century. In this comparison, semantic similarity analysis, one of the methods of the digital humanities, was applied to test the relationship between Abū Muḥammad 'Abdallāh's treatise De intellectu and the third book of Averroes' Long Commentary on Aristotle's De Anima. At the center of this methodological approach lies the aim of identifying conceptual and contextual overlaps between the two Latin texts by focusing on semantic similarity rather than on direct word matching. The similarity scores obtained through this method were evaluated as guiding indicators and were subjected to manual review to increase accuracy. Through this mixed approach, the claim in the literature that the treatise displays an Averroist approach was evaluated by means of both traditional close reading and digital methods. The findings show that the treatise is conceptually and contextually similar to the LCDA and is a summary of Averroes' theory of the intellect. However, it is also clear that Abū Muḥammad 'Abdallāh did not merely provide a summary, but also presented a text that brings together, within a certain unity, arguments found in different parts of the Long Commentary. As a result, this study demonstrates, through close reading supported by the quantitative data provided by digital methods, that the treatise functioned as an introductory text on the Averroes' doctrine of the intellect for Latin thinkers.